2021
DOI: 10.3389/fpsyg.2021.645418
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Anxiety and Depression in Predicting Cardiovascular Disease Among Patients With Type 2 Diabetes Mellitus: A Machine Learning Approach

Abstract: Cardiovascular disease (CVD) is a major complication of type 2 diabetes mellitus (T2DM). In addition to traditional risk factors, psychological determinants play an important role in CVD risk. This study applied Deep Neural Network (DNN) to develop a CVD risk prediction model and explored the bio-psycho-social contributors to the CVD risk among patients with T2DM. From 2017 to 2020, 834 patients with T2DM were recruited from the Department of Endocrinology, Affiliated Hospital of Harbin Medical University, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Indeed, this scale was used in many Chinese researches and showed good reliability and validity (57, 58). DNN is typically used to make a prediction or classification through a series of layers, each of which combines an affine operation and a non-linearity (41). The DNN consists of an input layer, an output layer, and several hidden layers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this scale was used in many Chinese researches and showed good reliability and validity (57, 58). DNN is typically used to make a prediction or classification through a series of layers, each of which combines an affine operation and a non-linearity (41). The DNN consists of an input layer, an output layer, and several hidden layers.…”
Section: Methodsmentioning
confidence: 99%
“…Deep Neural Network (DNN) is typically used to make a prediction through a series of layers, each of which combines an affine operation and a non-linearity. Studies showed that DNN models could provide an automated identification mechanism for various diseases, such as cardiovascular disease ( 41 ), diabetic retinopathy ( 42 ), neurological disorders ( 43 ), etc. Hence, in order to provide insights, augment prevention, and reduce risks in weight management among healthcare workers, there are great benefits of applying machine learning technology to develop a prediction model of BMI change among doctors and nurses during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…G-mean is often used to evaluate the effect of prediction classification model in unbalanced data ( 53 ). An AUC of 1.0 represents a perfect test, with no false positive rate and no false negative rate, while an AUC of 0.5 indicates that the test performed no better than chance ( 54 ). Moreover, we used mean impact value (MIV) to identify important predictors for suicidal ideation ( 55 ).…”
Section: Methodsmentioning
confidence: 99%
“…There is growing interest regarding the crucial role of clinical psychological factors in chronic conditions [1][2][3][4][5]. It is well known that psychological features may help predict medical diseases, referring to both personality traits and mood states (e.g., alexithymia, depression, anxiety) as well as conscious and unconscious strategies (e.g., coping, defense mechanisms) [6][7][8][9][10][11][12][13][14]. On one hand, chronic conditions and their linked outcomes could lead to psychological symptoms, compromising the patients' health-related quality of life (HR-QoL) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to several existing therapies [39][40][41][42], which have demonstrated specific efficacy in the treatment of osteoporosis by reducing fracture risk, it could be interesting to investigate, in postmenopausal women, the potential role of psychological features in determining and influencing the osteoporosis treatment response. As well, among several psychological features, anxiety seems to represent a meaningful vulnerability factor, since in chronic conditions individuals fear for the progressive loss of bodily intactness and are faced with managing the unexpected [2,6,8,13]. The aim of this study was to longitudinally investigate the association between anxiety levels and both adherence and treatment response to oral bisphosphonates (BPs).…”
Section: Introductionmentioning
confidence: 99%